Answer:
(5 - y) ^3 = 125 - 75y + 15y^2 - y^3
Step-by-step explanation:
Binomial expression
1
1. 1
1. 2. 1
1. 3. 3. 1 --------power of 3
( 5 - y) ^3
( 5 - y) (5 - y) (5 - y)
( a + b) ^3 = a^3 + 3a^2b + 3ab^2 + b^3
a = 5
b = -y
( 5 - y) ^2 = ( 5 - y) (5 - y)
= 5( 5 - y) - y(5 - y)
= 25 - 5y - 5y + y^2
=(25-10y+y^2)
( 25 - 10y + y^2)( 5 - y)
= 5(25 - 10y + y^2) - y( 25 - 10y + y^2)
= 125 - 50y + 5y^2 - 25y + 10y^2 - y^3
Collect the like terms
= 125 - 50y - 25y + 5y^2 + 10y^2 - y^3
= 125 - 75y + 15y^2 - y^3
Answer:
The correct option is A
Step-by-step explanation:
The given expression is:
√10/4√8
We have to eliminate the √ from the denominator
4√8 = (2^3)^1/4
Multiply the whole expression by (2)^1/4
=(2)^1/4 * √10/ 2^(1/4)*(2^3)^(1/4)
= 2^(1/4) · 10^(2/4) / 2^1/4+3/4
=2^(1/4) · 10^(2/4) / 2^1+3/4
=2^(1/4) · 10^(2/4) / 2^4/4
=2^(1/4) · 10^(2/4) /2
=2^(1/4) · 100^(1/4) /2
=200^1/4 /2
= 4√200 /2
Thus the correct option is A....
Answer:
1 solution
Step-by-step explanation:
Solution is, x=3-4y
Answer:
-8
Step-by-step explanation:
It's basically -4-4. Which means -(4+4) = -8.